The Relative Power of Negativity: The Influence of Language Intensity on Perceived Strength. (March 2019) - Liebrecht, Christine; Hustinx, Lettica; van Mulken, Margot
Negative utterances and words have been found to be stronger than positive utterances and words, but what happens if positive and negative utterances are intensified? Two online experiments were carried out in which participants judged the strength of (un)intensified positive and negative evaluations in written dialogues. Both studies showed intensified language was perceived as stronger than unmarked language (i.e., language that was not intensified), and negative evaluations were stronger than positive evaluations. What is more, intensification and polarity interact; the increment of perceived strength for intensified positive adjectives (Study 1) and purely intensified adverbs ( really, very ; Study 2) was bigger than the increment in perceived strength of intensified negative adjective and adverbs. When a meaningful intensifier ( deliciously, disgustingly ) was used, the negativity effect remained. The findings were discussed within cognitive frameworks such as relevance theory, theory of mind, and theory on verbal aggression.